the great man's send the ans
Attachments:
![](https://hi-static.z-dn.net/files/da0/592a4c1575c490a5edc94cc5849f231a.jpg)
Answers
Answered by
4
HEY MATE
HERE'S YOUR ANSWER
HOPE IT WILL HELP YOU
MARK ME AS BRAINLIEST
HERE'S YOUR ANSWER
HOPE IT WILL HELP YOU
MARK ME AS BRAINLIEST
Attachments:
![](https://hi-static.z-dn.net/files/d0c/37a03c7607457c35d5a2901b39de7134.jpg)
sharathshetty26:
įam not understand clearly please send good photo
Answered by
1
GIVEN:- tanθ/(1 - cotθ) + cotθ/(1 - tanθ)
=> tanθ/(1 - 1/tanθ) + (1/tanθ)/(1 - tanθ)
=> tan²θ/(tanθ - 1) - 1/tanθ(tanθ - 1)
=> 1/(tanθ - 1) { tan²θ - 1/tanθ }
=> 1/(tanθ - 1) { (tan³θ - 1)/tanθ)
[as, a³ - b³ = (a - b)(a² + b² + ab)
=> {(tanθ - 1)(tan²θ + 1 + tanθ)}/{(tanθ - 1)(tanθ)}
=> tanθ + cotθ + 1
=> sinθ/cosθ + cosθ/sinθ + 1
=> (sin²θ + cos²θ)/sinθ . cosθ + 1
=> 1/sinθ . cosθ + 1
=> cosecθ . secθ + 1
plz mark as brainliest
Similar questions